(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
"In recent decades, there has been an increasing need for robotic gripping device capable of sensitively handling things of varied forms. While classic finger-shaped gripping devices are adaptable and can grab a broad variety of things, achieving a firm hold without slippage demands precise alignment of the fingers on the object. This study offers the notion of a ring-like delicate gripper that wraps across items much resembles an elastic string. The implied gripper is constructed of a flexible tube having layers of sponges interspersed with plastic sheets. By emptying the air inside the sponges, they contract, lowering the ring’s diameter and permitting a tight grasp on things. This endows the gripper with the flexibility to wrap around items of varied forms flawlessly, leaving no opportunity for gaps. Moreover, the hardness of the compressed sponges inside the gripper mitigates any possible swaying of the grabbed items. Airborne particles inside The device that grips may be modified to fine-tune the grabbing energy. After air is emptied from the sponges, the gripper’s minimal diameter is roughly one-fourth of its initial size. Consequently, our suggested gripper is set to find applications across a range of sectors, giving the potential to simply and firmly hold things while seamlessly adjusting to their various forms."